EFEKTIVITAS PERKULIAHAN DARING MAHASISWA PROGRAM SARJANA STAI FATAHILLAH SERPONG - Windy Dian Sari; Tasya Sukma Maulidya; Putri Nurhasanah; Purniasih Purniasih (el-Moona: Jurnal Ilmu Pendidikan Islam, 2022)
When doing distance learning, of course, you need media as a learning tool. Currently, Indonesia is the country with the 4th largest number of internet users in the world and has an internet penetration of 73.7 percent of the total population or 202.6 million users. This is the background for conducting useful research to determine the effectiveness of online lectures for students of the STAI Fatahillah Serpong course program. This study uses a quantitative descriptive method. Descriptive research methods are not intended to test certain hypotheses, but to describe what a variable or situation is. In the results of interviews conducted using google form with respondents as many as 29 students, results were obtained stating that students had various complaints caused by lack of quota, poor network, inappropriate lecture times, and the lack of attractiveness of the courses taught.